Model of health services for future parents: a scoping review - Wiyanti, Zulvy; Astuti, Andari Wuri; Kit, Ayano; Fatimah, Siti (Jurnal Cakrawala Promkes, 2024)
The readiness of prospective parents plays a pivotal role in their journey toward parenthood, influencing their ability to navigate the transition smoothly. This readiness can be cultivated through comprehensive physical and mental health screenings, empowering them to embark on their parenthood journey with a well-prepared and healthier pregnancy plan. This scoping review aimed to identify previous research evidence regarding health service models for prospective parents. This research is a scoping review using Framework Arkshey & O’Malley and PRISMA-Scr Checklist, four journal databases: Pubmed, Wiley Online Library, EBSCO, and Proquest. Apart from that, this research also used Google Scholar and official sites that support it. The keywords used are models, health services, and future parents. Article quality assessment using MMAT (Mixed Methods Appraisal Tool). A total of 2,899 articles were checked for duplication and title screening, abstract screening. A total of 21 articles were screened for the whole article, and only 11 were deemed eligible. The results of this article is that health programs during the premarital and preconception periods are important in preparing a healthy generation. Each country has premarital and preconception health programs, including providing blood supplement tablets and folic acid, mental health screening, and genetic disease screening. It is expected that cross-sector collaboration could increase the use of health services during the premarital and preconception periods. These programs serve as crucial avenues for imparting essential knowledge and fostering positive behaviors that can significantly impact the health outcomes of both parents and their future offspring. By prioritizing proactive healthcare measures and education during these pivotal stages, society lays a robust foundation for promoting the well-being and vitality of future generations.